Identification of Challenges and Solutions in the Implementation of the Vision and Mission of Pancasila Student Profile Formation at Parlaungan Islamic Junior High School - Kesuma Dewi, Srie Wijaya; Masnawati, Eli (LP2M IAI Al-Khairat Pamekasan, 2024)
The formation of the Pancasila Student Profile has become one of the priorities in the Indonesian education sector at the moment. SMP Islam Parlaungan, as one of the private Islamic schools, is striving to implement the school's vision and mission in order to achieve a student profile that is in accordance with the values of Pancasila. This study aims to identify the challenges and solutions in the implementation of this vision and mission. The research method used is a qualitative approach with data collection techniques through observation, interviews, document analysis, and surveys. The data obtained is then analyzed descriptively to identify the challenges faced and formulate appropriate solutions. The research results show several main challenges, including: (1) uneven understanding of teachers regarding the Pancasila Student Profile, (2) lack of adequate supporting facilities and infrastructure, (3) limited time in integrating the values of Pancasila in learning activities, and (4) lack of parental involvement in supporting the formation of the Pancasila Student Profile. The recommended solutions include improving teacher training and development, procuring more adequate facilities, curriculum adjustments, and closer collaboration between schools, parents, and the community. This research is expected to provide valuable input for the school in an effort to optimize the implementation of the vision and mission in forming the Pancasila Student Profile at SMP Islam Parlaungan.